Features of perception of the family by children of preschool age (Actual Problems of Psychology in Educational Institutions, 2022)
The article reveals the peculiarities of the perception of the family by children of preschool age. The influence of family functions is determined on the development of the child's personality. A research was conducted to determine the influence of emotional atmosphere in the family on preschoolers. The emotional connection with parents is analyzed.